2008
DOI: 10.1246/cl.2009.2
|View full text |Cite
|
Sign up to set email alerts
|

Task Specific Ionic Liquids for Cellulose Technology

Abstract: Design of ionic liquids for dissolution, depolymerization, and energy conversion of cellulose and their derivatives is described. Importance of physicochemical properties such as polarity and hydrogen-bonding ability of the ionic liquids is described, and some practical approaches to prepare novel ionic liquids as solvents for cellulose technology are reviewed with latest results. Ç IntroductionThe energy crisis is a major concern. There have been many discussions of substitute materials to replace petroleum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
159
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 300 publications
(164 citation statements)
references
References 56 publications
3
159
1
1
Order By: Relevance
“…A slight shielding of the methylene carbons in the α position were also observed when converting the amine δ = 45.9 ppm (2C) and δ = 54.8 ppm (1C) to the IL δ = 45.3 ppm (2C) and δ = 54.6 ppm (1C PO 4 ] were also selected based on their subtle differences in polarity and substituent effects. The polarity of an IL has been correlated with its ability to solubilize both lignin (42,43) and cellulose (44)(45)(46) PO 4 ] were used to dissect the role of these substituents on the relative acidity of the cation and relate these effects to biomass pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…A slight shielding of the methylene carbons in the α position were also observed when converting the amine δ = 45.9 ppm (2C) and δ = 54.8 ppm (1C) to the IL δ = 45.3 ppm (2C) and δ = 54.6 ppm (1C PO 4 ] were also selected based on their subtle differences in polarity and substituent effects. The polarity of an IL has been correlated with its ability to solubilize both lignin (42,43) and cellulose (44)(45)(46) PO 4 ] were used to dissect the role of these substituents on the relative acidity of the cation and relate these effects to biomass pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11] Furthermore, many liquid-liquid phase equilibrium systems such as IL/water and IL/ organic solvent systems have been presented; this indicates the possibility of utilizing ILs as reaction or extraction solvents. [12][13][14][15] For example, it has been shown that 1-alkyl-3-methylimidazolium bis(trifluoromethane sulfonyl)amide ([C n mim][NTf 2 ]), a typical hydrophobic IL, can be used for the extraction of aromatic compounds from aliphatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…First article on the cellulose depolymerization in ionic liquids was reported by Rogers et al 25 Ohno et al proposed a cellulose-based energy conversion process using the RTIL treatment in order to generate electrical energy from cellulose that cannot be decomposed under a mild chemical process. 26 Recent years, several research groups have attempted to directly liquefy wood in RTILs so as to yield glucose. 27,28 However, there is a limited number of articles on the liquefaction mechanism of wood.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that RTILs showing the high ¢ value can dissolve cellulose with ease. 26 The liquefaction experiment of the wood (Cryptomeria japonica) was conducted at less than 393 K. Figure 5 shows SEM images of the cross-sectional wood sample pretreated with the Scheme 1(b) before and after the liquefaction process of the wood. Before the liquefaction process, two different parts, earlywood and latewood, were observed clearly [ Fig.…”
Section: Resultsmentioning
confidence: 99%